2002
DOI: 10.1007/s11664-002-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-selectivity process for electron cyclotron resonance plasma etching of II-VI semiconductors

Abstract: The erosion rate of resist during electron cyclotron resonance (ECR) plasma etching of II-VI semiconductors is the limiting factor for the selectivity (values range from 5:1 to 10:1). We have measured the erosion rates of AZ 1529, a commercially available diazonaphthoquinone (DNQ) novolak photoresist, under plasma conditions optimized for etching of the underlying semiconductor and have developed an in-situ technique to "harden" the resist by exposing it to an argon-only ECR plasma. A subsequent standard plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…5,8,[11][12][13]15 However, to better control the compound semiconductor removal rate an unbalanced plasma etch can be used. If one of the semiconductor's constituents is removed more slowly than the others, this will limit the removal rate for the entire compound.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,[11][12][13]15 However, to better control the compound semiconductor removal rate an unbalanced plasma etch can be used. If one of the semiconductor's constituents is removed more slowly than the others, this will limit the removal rate for the entire compound.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, ICP plasma processing, used in HgCdTe, is still maturing and continued research is needed. 4,7,14 ICP plasma processing may also be used to replace conventional wet chemical clean-up, and even be used in the surface preparation for epitaxy of II-VI materials.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,11 Argon to hydrogen gas ratio of 4:1 with a DC bias input power of 60 W was used for these studies. The average ion energy has been previously determined to be Ϸ15 eV for these plasma conditions.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Several studies have also reported the effect that high-density ''dry'' electron cyclotron resonance (ECR) plasmas have on HgCdTe epitaxial properties. [5][6][7][8][9][10][11][12][13][14] However, ICP plasma processing, for use in HgCdTe, is still maturing and continued research is needed. 4,7,14,15 ICP plasma processing may also be used to replace conventional wet chemical clean-up, and can even be used in the surface preparation for epitaxy of II-VI materials.…”
Section: Introductionmentioning
confidence: 99%